Pengaruh Media Pembelajaran Berbasis Alam terhadap Motivasi Belajar Anak Kelompok B - Yuwita Dabis; Irvin Novita Arifin; Rapi Us. Djuko (Student Journal of Early Childhood Education, 2022)
The purpose of this study was to determine the effect of nature-based learning media on the learning motivation of group B. This study is experimental quantitative research (one group pretest-posttest design). This study used a sample of 25 children. The result of research that has been done, the pretest data obtained and average value of 17,52 and the posttest data obtained an average value of 34,48. These results indicate that there is an influence of nature-based learning media on the learning motivation of group B.